2019
DOI: 10.1002/ps.5376
|View full text |Cite
|
Sign up to set email alerts
|

Selection and characterization of the inheritance of resistance of Spodoptera frugiperda (Lepidoptera: Noctuidae) to chlorantraniliprole and cross‐resistance to other diamide insecticides

Abstract: BACKGROUND Understanding the genetic basis of insect resistance to insecticides can help to implement insecticide resistance management (IRM) strategies. In this study, we selected a strain of Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) resistant to chlorantraniliprole using the F2 screen method, characterized the inheritance of resistance and evaluated patterns of cross‐resistance to other diamide insecticides. RESULTS The chlorantraniliprole‐resistant strain (Chlorant‐R) was selected from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
151
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 174 publications
(173 citation statements)
references
References 58 publications
4
151
0
11
Order By: Relevance
“…A low frequency of resistance to chlorantraniliprole has been reported in Brazilian field populations of FAW collected in 2012, 2013 and 2014 . More recently, a F2 screen and subsequent laboratory selection resulted in a FAW strain, Chlorant‐R, showing high levels of diamide resistance . The genetics of resistance in this strain was characterized as monogenic, incompletely recessive, and it has been shown that some heterozygotes would survive field‐recommended rates of chlorantraniliprole, thus increasing the risk of rapid evolution of resistance .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A low frequency of resistance to chlorantraniliprole has been reported in Brazilian field populations of FAW collected in 2012, 2013 and 2014 . More recently, a F2 screen and subsequent laboratory selection resulted in a FAW strain, Chlorant‐R, showing high levels of diamide resistance . The genetics of resistance in this strain was characterized as monogenic, incompletely recessive, and it has been shown that some heterozygotes would survive field‐recommended rates of chlorantraniliprole, thus increasing the risk of rapid evolution of resistance .…”
Section: Discussionmentioning
confidence: 99%
“…Diamide resistant (Chlorant‐R) and susceptible (Sus) strains of S. frugiperda were maintained under controlled conditions (25 ± 1 °C, 70 ± 10% relative humidity (RH) and 14:10 h light/dark photoperiod). Strain Chlorant‐R was maintained under continuous selection pressure by chlorantraniliprole as described previously …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations